2008
DOI: 10.1159/000115887
|View full text |Cite
|
Sign up to set email alerts
|

Sensitization and Allergy to <i>Cannabis sativa</i> Leaves in a Population of Tomato <i>(Lycopersicon esculentum)</i>-Sensitized Patients

Abstract: Background: Cases of allergy to Cannabis sativa have occasionally been reported, but both the allergenic profile and eventual cross-reactivity pattern remain unknown. Objective: To analyze the allergenic profile of a population of patients from Spain sensitized to C. sativa and to characterize the C. sativa leaf extract. Methods: A total of 32 subjects were enrolled in the study: group A, 10 individuals sensitized to tomato, reporting reactions by contact or inhalation to Cannabis; group B, 14 individuals sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 41 publications
2
35
1
Order By: Relevance
“…6 Paradoxically, the protective action of cannabis against allergies has also been described. 7 Cross-reactivity between cannabis and tomato allergens 8 and skin lesions due to inhalation of cannabis have been reported. 9 Allergic hypersensitivity to tobacco has been demonstrated by our group in a large series of patients.…”
Section: Discussionmentioning
confidence: 99%
“…6 Paradoxically, the protective action of cannabis against allergies has also been described. 7 Cross-reactivity between cannabis and tomato allergens 8 and skin lesions due to inhalation of cannabis have been reported. 9 Allergic hypersensitivity to tobacco has been demonstrated by our group in a large series of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Larramendi et al (2013) described six different bands with a molecular weight of 10-, 14-, 20-, 35-, 38-and 60-kDa that were recognized by the individual patients' sera. The 10-kDa IgE-binding band was already described in other reports (de Larramendi et al 2008;Gamboa et al 2007;Tanaka et al 1998) and most likely corresponds to Can s 3, the ns-LTP of C. sativa (Gamboa et al 2007) that belongs to the pathogenesis-related proteins (PR)-14 group (Van Loon 1999). In a study by Armentia et al (2014), sensitization to the purified cannabis ns-LTP was observed in 124 out of 130 patients (95.3 %) with a primary cannabis allergy.…”
Section: Cannabis Allergensmentioning
confidence: 54%
“…Although in the study of Larramendi et al (2013), no homology was found between the 14-kDa band and any known allergen, it was speculated that this band could be a profilin (de Larramendi et al 2008).…”
Section: Cannabis Allergensmentioning
confidence: 95%
See 1 more Smart Citation
“…1 As a result of the increasing social and medical usage, reports of allergic sensitization to marijuana are increasing in the peer reviewed literature. [2][3][4][5][6][7][8][9][10] Cases have been reported where hypersensitivity and even anaphylactic responses have been associated with marijuana use and clinical symptoms include sore throat, nasal congestion, rhinitis, pharyngitis, wheezing, dyspnea, angioedema and lacrimation. 2-4, 11, 12 In chronic and high dose users more severe manifestations of bronchitis and asthma with reduced vital capacity have been reported.…”
Section: Introductionmentioning
confidence: 99%